21st-Century Photobook as a Biographical Episode: Photographer’s Biography as a Subject for a Photobook - Romakina, Maria A. (Actual Problems of Theory and History of Art, 2018)
The paper investigates a special type of photographic works — photobooks with the plot focused on biographical facts from the lives of their creators, artistically reinterpreted. The specificity of this kind of photobooks is analyzed on the examples of a certain number of works produced by international authors in the 2010s. The main criteria of analysis are the content, the form, the visual style, and the narrative structure. These works were selected from the set of photobooks that won international competitions, participated in international festivals, or were included in curatorial collections published by authoritative media at the end of each year in the form of lists of the best works of that year. The author positions them as a special kind of art objects which — at the level of artistic transformation of the raw material — bear some similarities to documentary cinema and performative art forms. Such photobooks mark one of the significant trends in the field of visual practice: the investigation of biographies as resources for artworks and biographical artificial narratives. If previously the autobiographical form was available to the individuals, today it is actually mass practice. The form of the photobook as one of the most democratic ways of demonstrating an art message within the modern photographic market allows large numbers of authors to be included in the international art process, often bypassing the need for interaction with authoritarian institutions. The photobook returns to the photographic product a tangible material form. Moreover, the invention of its material essence is as important to the author as the creation of the photographic message itself. Thus, the photobook is a complex syncretic media-text with the special significance of its object essence and intimate space within it.
Keywords: photobook; photography; visual narrative; biography; memory; archive; materiality; performativity